Inconsistent Reporting of Discrimination Over Time Using the Experiences of Discrimination Scale: Potential Underestimation of Lifetime Burden. Issue 3 (21st May 2021) - Van Dyke, Miriam E; Kramer, Michael R; Kershaw, Kiarri N; Vaccarino, Viola; Crawford, Natalie D; Lewis, Tené T
Abstract: Studies documenting self-reported experiences of discrimination over the life course have been limited. Such information could be important for informing longitudinal epidemiologic studies of discrimination and health. We characterized trends in self-reports of racial, socioeconomic status, and gender discrimination over time measured using the Experiences of Discrimination Scale, with a focus on whether individuals' reports of lifetime discrimination were consistent over time. Overall experiences of discrimination and the number of settings in which discrimination was reported in 1992, 2000, and 2010 were examined among 2, 774 African-American and White adults in the Coronary Artery Risk Development in Young Adults (CARDIA) Study. Reports of "ever" experiencing discrimination decreased for all forms of discrimination across the 3 study visits. Approximately one-third (30%–41%) of the sample inconsistently reported ever experiencing any discrimination over time, which contributed to the observed decreases. Depending on the form of discrimination, inconsistent reporting patterns over time were more common among African-American, younger, less educated, and lower-income individuals and women—groups who are often most exposed to and severely impacted by the health effects of discrimination. Our findings highlight the possible underestimation of the lifetime burden of discrimination when utilizing the Experiences of Discrimination Scale to capture self-reports of discrimination over time.